A paixão do acesso: uma etnografia das ferramentas digitais e da jurisprudência do Superior Tribunal de Justiça - Munhoz, Sara Regina (2022)
This thesis is dedicated to optical mechanisms that enable the enunciation of Brazilian jurisprudence. To effectively occupy its authority position, the Brazilian Superior Court of Justice (SCJ) needs, on one hand, to remove from its visualization field the excesses and minutiae of what occurs in the “factual world”, focusing exclusively on legal arguments. To that end, the Court erects barriers to control the entry of numerous processes, but those cancels simultaneously add complexity to assessing several other factors, such as affection and intention when family case laws are at play. On the other hand, it is also pivotal that the legal arguments sustained by the SCJ are adequately disclosed to guarantee persuasive, expandable, and replicable statements. Ministers’ interpretation regarding what determines the law, once enacted, should settle as an order capable of transiting within the entire national justice system, avoiding that similar conflicts disturb ministers in further decision- making. By examining a heterogenous cluster of SCJ technical-administrative files, this thesis describes how analysts and computers, far from the ministers’ offices, take charge of comparing and compartmentalizing sentences, generating hyperlinks, and producing Mirrors and Products that are available as jurisprudence to users (i.e., the ministers themselves, lawyers, or citizens) through a digital searching engine. Enabling access to SCJ understanding is a guarantee of accessible, safe, and democratic justice. Therefore, by focusing on bureaucratic circuits and digital syntheses subsequent to the judgments of one of the most important Brazilian courts, this thesis expands the already consolidated outreach of a bibliography dedicated to the technical production of law, including its current and thorough interconnection with information technology, without which the SCJ can no longer judge.